Field reports form for submitting seasonal observations of Iowa birds, Ronald Harms, fall 1983 - Harms, Ronaldet al (1983)
An annotated list of birds sighted by Ronald Harms and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1983. Epson - sheet feed